Reasons for encounter and diagnosis in patients seen in Limpopo Province primary health care : a prospective cross-sectional survey - Omozuanvbo, Ikpefan Ewan (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.